MOTIVATING YOUNG LEARNERS IN THE EFL CLASSROOM AT THE UNIVERSITY - Meyliyeva Shafoat Erali qizi (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
Motivating EFL students to develop in the target language is very challenging. In many cases, these students face difficulties in learning English and are often demotivated to learn. Research in classroom motivation has found that exact strategies can help these students adopt more positive attitudes and become more motivated in the learning process. This study investigates the perceptions through interviewing students and surveying teachers’ views in an EFL Program of the problems that hinder these students’ learning in the English classes related to motivation. Findings show that learners are not motivated to learn English because of an over-focus on writing skills with very little new learning experiences, uninteresting materials, and unclear links between language courses and their majors or future careers. Results also indicate that teachers complain of unmotivated students and pre-structured syllabi leaving little room for communicative methods.